Rust [videorecording (DVD)] - Baldwin, Alec, 1958-; Hopkins, Josh, 1970-; McDermott, Scott; Fimmel, Travis, 1979-; Fisher, Frances, 1952- (Decal Partners, 2025)
A 13 year-old boy, left to fend for himself and his brother following the death of their parents, is taken on a harrowing journey to old Mexico by his estranged grandfather after he's sentenced to hang for an accidental killing.